Archívumok és újrajátszás: A szolidáris emlékezés stratégiái Radu Jude műveiben - Dánél, Mónika (Studia Litteraria, 2024)
The paper analyses and (re)structures the works of contemporary Romanian director Radu Jude with heavy focus on the re-enactment. On the one hand, Jude’s films reflect on contemporary media conditions and their influence on society investigating different types of advertising as re-enactment processes (Do Not Expect Too Much from the End of the World, 2023, 4e Happiest Girl in the World, 2009); on the other hand, his artworks as intermedial collage constellations create social platforms for mnemonic solidarity for silenced and unprocessed social traumatic past events. As a socially engaged artist Jude analyses the historical, media and consequently mental legacies of Romanian society regarding the Holocaust. In his documentary collage films combining photographic and acoustic (e. g. military songs) archives, diaries read out by the director himself (4e Dead Nation, 2017), conflicting photo archives, re-enacted statements and testimonies documenting the Pogrom in Iaşi in June 1941 (4e Exit of the Trains, 2020) Jude is enabled to create structurally open intermedial constellations, which turn into a re-animated and re-enacted experience by the viewer’s implication. ese sites of mnemonic solidarity reflect on the “implicated subject” (Michael Rothberg) position of contemporary society as well as on our current implicated positions, including the director’s position as a responsible agent in the process of image production and visual conditioning (especially in I Do Not Care If We Go Down in History as Barbarians, 2018).